Limit Condition for the Intermunicipal Emergency - Di Lodovico, Luana; Di Ludovico, Donato (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The traditional urban planning issues, related to the design and city shape, today are faced with those derived from safety and risk. The Emergency Plan (EP) is the result of study about risk for each context, and it allows to identify potential emergency scenarios. The paper illustrates model of analysis of Intermunicipal Emergency Plan (I-EP) through Limit Condition for the Intermunicipal Emergency I-LCE), with the purpose of large-scale assessment and mitigation of the seismic risk. This is an approach that extends the methodological principles of Limit Condition for the Emergency (LCE) to the territory, we consider that the EP, in the same way as urban planning, is not a planning activity that can be concentrated only on urban area but must work on the "territory system", especially for the effect control of natural phenomena such as seismic risk. This not only threatens a significant innovation for the LCE but also for its relationship whit the urban planning its design strategies aimed at reducing territorial fragilities. The proposed methodology is applied in the area of Sele, in the district of Salerno (Southern Italy), territory characterized by high levels of seismic and hydrogeological vulnerability. Through this case study we had the opportunity to discuss the potential of I-LCE and its additional recommended updates to increase its effectiveness and efficiency, in addition the necessary innovations of urban and territorial planning systems.